Antidumping, Retaliation Threats, and Export Prices - Avsar, Veysel (Oxford University Press on behalf of the World Bank, 2014)
Utilizing four-dimensional (firm-product-destination-year) Brazilian firm-level export data, we show that antidumping (AD) duties result in a significant and dramatic increase in the unit values of the products that firms export to duty-imposing countries. Furthermore, we examine the effect of potential (retaliatory) AD duties on the unit price of the firms' shipments. Our findings suggest that AD activities in Brazil lead Brazilian exporting firms to increase their unit export prices for the named industries' products to decrease the dumping margin and avoid the threat of retaliation by the target countries.